Structural and functional changes in early successional stages of a semiarid ecosystem - Redente, Edward F., author; Cook, C. Wayne, author; Department of Range Science, Colorado State University, publisher (Colorado State University. Libraries, 1986)
The objective of our research is to study structural and functional changes that occur within and between ecosystem compartments during secondary succession in disturbed semiarid environments. This information not only will assist in better understanding fundamental aspects of these processes, but should lead to more effective management of these disturbed semiarid environments. First year data clearly showed an increase in resource abundance after disturbance which produced not only alteration of the soil surface but a decrease in available organic matter. In addition, marked increases in NO3- and soil water potentials were evident at all depths in the disturbed sites as compared to the undisturbed community. Potential N mineralization rates, a measure of plant-available N, primarily from microbial biomass did not differ, but actual mineral N levels were higher because of higher soil moisture. Water use efficiency also varied with the early successional species being more efficient than late successional species. However, the late successional species were able to effectively use water under lower soil water potentials. These results are consistent with available information showing that "climax" species are less efficient in producing biomass at high levels of resource availability but able to sustain growth under conditions of nutrient (including water) stress. Soil disturbance as well as manipulation of the microflora compartment by fumigation had a significant impact on microflora structure and function, and could have a long term impact on resource availability which will be important in understanding microbial contributions to the early development of plant-soil systems. Soil enzymatic activity, phosphatase, dehydrogenase and especially N fixation, ammonium and nitrite oxidation were still markedly reduced by disturbance and fumigation. This reduction of nutrient cycling, together with the elimination of plants, resulted in a sharp decline in fungal species diversity, with the saprobic community being dominated by pioneering species like Penicillium, Phoma, and Cladosporium. The mycorrhizal population was also drastically reduced by disturbance and fumigation. With plant community development, the level of mycorrhizal inoculum potential (MIP) was lower with ruderal (R) and competitive-ruderal (C-R) plants while higher MIP values occurred when the plant community was dominated by stress tolerant plants (S). MIP was also inversely correlated with the level of non-rhizosphere microbial activity. A preliminary study of rhizosphere vs. non-rhizosphere microbial development was conducted in the field in this first growing season where cheatgrass (Bromus tectorum) and western wheatgrass (Agropyron smithii) responses, with and without fertilization, were evaluated. The rhizosphere of both plants had consistently higher microbial populations, enzymatic activity, and fungal diversity than the non-rhizosphere. The rhizosphere of cheatgrass showed higher microbial population and enzymatic activities and lower diversity than the rhizosphere of western wheatgrass. These preliminary studies conducted with an annual versus a perennial plant will be examined in greater detail in comparison with other perennial plant responses in the corning year. The floristic composition of the primary producers on the disturbed site was highly correlated. With the propagule supply, with composition of the seed bank being the main driving force. Resource competition was not important at this stage in determining species composition because plant density was low and N, P, and water resources were abundant. Total aboveground net primary production (NPP) was similar in undisturbed and disturbed plots but the structure of primary producers was significantly different. The disturbed sites were dominated by plants with an R and CR strategy while the undisturbed sites were dominated by plants with an S strategy, indicating strong relationships between plant composition and soil resource abundance. Competition studies between bluebunch wheatgrass (Agropyron inerme), western wheatgrass, big sagebrush (Artemisia tridentata), and winterfat (Ceratoides lanata) showed that these four species were able to coexist under a wide range of water availability conditions. This appeared to be related to differences in carbon allocation to shoots t roots, and sterns and an ability to control water losses among these plants. The grasses showed a faster rate of growth and root expansion than shrubs during the establishment phase and as a result, competition between grasses was more intense than between shrubs or grasses and shrubs, leading to a decline in biomass production. Competitive relationships of mature species in the natural community were in some instances different than those found in greenhouse experiments. For instance, winterfat competed better with western wheatgrass than with another winterfat because winterfat could use water deeper in the profile, which was not available to the grass. Under field conditions, the water status of all plants was more favorable on deeply disturbed soils, than on shallowly disturbed soils and varied carbon allocation patterns, stomatal conductance, and transpiration rates were also evident. The final phase of an experiment designed to determine the effects of retorted shale recarbonation on plant uptake of toxic trace elements was completed. Plants grown on recarbonated retorted shale had significantly lower concentration of B, Ba, and Sr and higher Mo levels than plants grown in non-recarbonated shales. In contrast, As, Cr, F, and Ni uptake was below toxic levels with and without recarbonation. The Cu:Mo ratio in plants was not influenced by recarbonation, being below the recommended levels for utilization by ruminants. This represents a potential source of toxicity which will not be influenced by the recarbonation process. These initial studies, in summary, indicate that both plant community characteristics and the presence of a functioning belowground community will be important in secondary succession processes which occur in disturbed semiarid environments. Rhizosphere and nonrhizosphere microflora structure and dynamics as well as plant competition strategies, as influenced by nutrient resource availability, will be critical factors influencing the successional process.
Prepared for the U.S. Department of Energy.
Submitted February 1986.
Keywords: Biotic communities; Shale oils